Distribution of the Pearl Oyster Pinctada maxima off Eighty Mile Beach, Western Australia - Whalan, Steve; Puotinen, Marji; Wakeford, Mary; Parnum, Iain; Miller, Karen (Frontiers in Marine Science, 2021)
The silver-lipped pearl oyster, Pinctada maxima, is the primary species used for the culture of pearls in the Indo-Pacific region. The Western Australian fishery relies on wild-caught animals, and as such, knowledge of the status and distribution of P. maxima underpins sustainable management of the fishery. Eighty Mile Beach, in tropical Western Australia, is the key harvest area for P. maxima, with oysters collected by divers to depths of ~35m, although there are anecdotal accounts of oysters beyond diving depths. Image-based, and acoustic methods were used to elucidate distribution patterns of P. maxima off Eighty Mile Beach, including data from 862 km2 of multibeam survey and 119 towed video transects spanning an area from the 20m to 100m contour lines. We quantified habitat characters including depth, substrate, and benthic community composition associated with pearl oyster distribution. Multibeam sonar data was also coupled with towed video data to produce predictive statistical models of P. maxima habitat. We found P. maxima to depths of 76 m, although more than 90% of individuals occurred shallower than 40m and less than 2% were found deeper than 50 m. Oysters occupied flat, sandy habitats with neighbouring benthic communities of filter feeders (>98% of observations). These results show P. maxima predominantly occurs in depths <40m, with no evidence that extensive populations extend into deep water in the region.